Estudo comparativo entre a colpocitologia e a reação em cadeia de polimerase para o diagnóstico do papilomavírus humano no colo uterino de mulheres portadoras do vírus da imunodeficiência humana - Iwens Moreira de Faria (2007)
Objective: to check the acuity of cytologic exam for the HPV diagnosis, from cytology of the uterus of HIV women, through comparison with the polymerase chain reaction method (PCR). Methods: a hundred and fifty-eight HIVPositive patients, from whom a material collection (exfoliated) was carried out of uterine cervix for a PCR and cytology with Ayre and Cytobrush spatula, were studied. Of this total, 109 smears were revised, because 49 had been destroyed for having exceed 2 years of archive. Results: among the 158 patients, HPV prevalence was 11,0% through cytologic study and 69,7% through PCR. The age of the studied group ranged from 20 to 61 years old with an average of 35 years old. HIVcontamination was heterosexual in 91,8% of cases and 79,1% of patients had from 1 to 5 sexual partners in their lifetime. The most common complaint was pelvic mass (5,1%) and 75,3% looked for routine visit. Among 76 patients with HPV detected by PCR, only 12 were confirmed by cytology (S = 15,8%). This didnt show any false-positive (E = 100%).Comparing the two results, it was found for cytology: Positive Preditive Value = 100% and Negative Preditive Value = 33,3%. Among 12 patients with Positive Cytology for HPV, 4 (33,3%) showed neoplasia intraepithelial cervical (NIC), odds ratio 5,6. Positive ratio likelihood = positive infinity and negative ratio likelihood = 0,83. Conclusion: as cytology specifity is very high and sensitivity is low, it means that when cytology is positive, HPV will certainly be present. The low sensitivity retrieves from cytology the value as screening for HPV test in this group of women.